Preparação, caracterização e aplicação do ZnO para produção de radioisótopos de gálio - Cristiana Perdigao Rezende (2011)
Zinc oxide, ZnO, has attracted interest in various areas of research by enabling a wide range of industrial applications which may provide advances in areas electronic, medical and pharmaceutical industries.In this paper we present a study of the properties of zinc oxide obtained byprecipitation method with variations on the routes of synthesis (precursor:Zn(NO3)2.6H2O; Zn(CH3COO)2.2H2O; ZnCl2 and precipitating agents Na2CO3 and NH4OH) and drying (oven and freeze dryer). These samples were heat treated. The influences of these changes in the structure, morphology and texture of the nanoparticles obtained were studied with the aid of thermal analysis techniques, Xraydiffraction, infrared absorption spectroscopy, gas adsorption and scanning electron microscopy. The nanoparticles obtained from zinc acetate with ammonium hydroxide were pressed and tested in a study of sintering of powders in order to correlate the grain growth with the type of precursor, temperature and sintering time. Evaluation of thegrain growth and densification, as well as the influence of porosity on themechanical properties of these ceramics were made in order to obtain a material with characteristics suitable for production of radioisotopes for targets. The commercial ZnO would not be suitable for irradiated target for obtaining gallium because it has heterogeneous particles, which is not conducive to sintering. Because of this, there is the importance of this work in search of a nanoparticulate material with characteristics suitable for production of radioisotopes for targets.